Jesuit architecture in Japan: how to convert a Buddhist temple into a church - Higashino, Adriana Piccinini (2016)
The Jesuits arrived in Japan in 1549 and until their expulsion were very active, converting people to Christianity, building churches, schools, and hospitals. The Jesuits relied on the local lords’ financial support to build and often received Buddhist temples to be converted into churches. Based on a review of Jesuit letters, a brief analysis of Japanese Buddhist temple floor plan characteristics, a short review of Jesuit church architecture in general and in Japan I will illustrate how a Buddhist temple floor plan may have looked like when converted into a Jesuit church.